1976
DOI: 10.1007/bf00499215
|View full text |Cite
|
Sign up to set email alerts
|

A possible common mechanism of action of antidepressant treatments

Abstract: The response of the noNEpinephrine (NE) sensitive cyclic AMP generating system in slices of the rat limbic forebrain after both the acute and chronic administration of the tricyclic antidepressants desipramine (DMI) and iprindole as well as electro-convulsive treatment (ECT) was investigated. Neither the basal level of cyclic AMP nor the hormonal response to NE were altered after administration of a single dose of short term treatment with DMI and iprindole. However, the administration of the antidepressants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 411 publications
(58 citation statements)
references
References 23 publications
6
52
0
Order By: Relevance
“…These adaptive changes at the level of central adrenergic receptors might be interpreted as a response to sustained elevated levels of extracellular NE in the NET À/À mice, which has indeed been shown by Wang et al (1999) and Xu et al (2000). In many studies, it has been reported that repeated treatment with tricyclic ADs or electroconvulsive shock increases either the density or agonist affinity of brain a 1 -adrenergic receptors (Menkes and Aghajanian, 1981;Menkes et al, 1980;Nalepa et al, 2002;Vetulani et al, 1984). However, not all investigators have been able to confirm the above findings (Heal, 1984;Stockmeier et al, 1987;Hayakawa et al, 1992), indicating that variables involved have not been completely isolated.…”
Section: Discussionmentioning
confidence: 77%
“…These adaptive changes at the level of central adrenergic receptors might be interpreted as a response to sustained elevated levels of extracellular NE in the NET À/À mice, which has indeed been shown by Wang et al (1999) and Xu et al (2000). In many studies, it has been reported that repeated treatment with tricyclic ADs or electroconvulsive shock increases either the density or agonist affinity of brain a 1 -adrenergic receptors (Menkes and Aghajanian, 1981;Menkes et al, 1980;Nalepa et al, 2002;Vetulani et al, 1984). However, not all investigators have been able to confirm the above findings (Heal, 1984;Stockmeier et al, 1987;Hayakawa et al, 1992), indicating that variables involved have not been completely isolated.…”
Section: Discussionmentioning
confidence: 77%
“…The first group ("chronic DMI, high") received, by gavage, DMI-HCl at 50 mg/kg in 2 ml of tap water once daily for 3 days, and then 30 mg/kg per day thereafter for [7][8][9][10][11] days. The second group ("chronic DMI, low") received DMI at 30 mg/kg per day for [8][9][10][11][12][13][14][15][16][17][18] days.…”
Section: Methodsmentioning
confidence: 99%
“…The second group ("chronic DMI, low") received DMI at 30 mg/kg per day for [8][9][10][11][12][13][14][15][16][17][18] days. These two "chronic groups" were tested electrophysiologically [24][25][26][27][28][29][30][31][32][33][34][35][36] hr after the last dose, when cerebellar DMI is roughly one-half the level during treatment (unpublished data). The third group ("controls") received 2 ml of tap water by gavage daily for [6][7][8][9][10] days.…”
Section: Methodsmentioning
confidence: 99%
“…Firstly, in common with many other antidepressant treatments, repeated ECS administration decreases P-adrenoceptor number (Bergstrom & Kellar, 1979;Deakin et al, 1981) and noradrenaline-sensitive adenylate cyclase activity (Vetulani et al, 1976). Secondly, it attenuates both the sedation response of rodents to the M2-adrenoceptor agonist clonidine and the decrease in brain 3-methoxy-4-hydroxyphenylglycol sulphate (MOPEG-SO4) concentration produced by this drug (Heal et al, 1981), suggesting a decrease in the function of the, possibly, presynaptic a2-adrenoceptors in the brain.…”
Section: )The Macmillan Press Ltd 1985mentioning
confidence: 99%